Bridging to transplant with azacitidine in juvenile myelomonocytic leukemia: a retrospective analysis of the EWOG-MDS study group - Cseh, Anna-Maria; Kulozik, Andreas (Blood, 2015)
To the editor: DNA methyltransferase-inhibiting azanucleosides have become a mainstay of treatment of myeloid neoplasms in adult patients,[1][1] with 5-azacytidine (azacitidine) being the agent in broadest clinical use. Although not curative, treatment with azacitidine achieves hematologic
Gesehen am 13.07.2017